Making the most of water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Nissen-Peterson, E., 1987 Rain Catchment and Water Supply in Rural Africa Edward Arnold. London with the Danish National Fund for Developing Countries. ISBN 0 340 28429 3